How many Italies? - Roberto Cellini; Antonello Eugenio Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The paper analyses the evidence about the growth of the Italian regions over the period 1970-91; in particular it studies the beta-convergence across regions, the convergence of each region towards its possible steadystate equilibrium path and the existence of groups of regions sharing the same stochastic trend. Besides the specific results on Italian regions, the paper provides and analyses some applications of different econometric methods for the investigation of the growth process.
Keywords: 330